The Concept of Multicultural Education According to the Book of Wasathiyah by Muhammad Abu Al-Fath Al-Bayanuni - Rima Nur Ekawati; Riska Rofikoh; Opik Abdurrahman Taufik; Basuki (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2023)
Multiculturalism education is the basis for developing a country with a plural society system. Multicultural education helps the world of education achieve educational goals and teaches multicultural education in schools. This study uses library research. Data sources include: secondary primary data sources. Primary data source: multicultural education model in the Wasathiyah book by Muhammad Abu Al-Fath Al-Bayanuni. And secondary sources of previous research results related to multicultural Islamic education which are published in national and international journals. The data will be analyzed by content analysis method. The Book of Wasathiyah by Muhammad Abu Al-Fath Al-Bayanuni which can be applied in multicultural education is an attitude of piety to Allah, having noble character towards fellow human beings, being devoted to parents, and not making differences in understanding religion and sect in life. Schools and the general public for multiculturalism education to provide awareness from an early age so that they can be placed in a middle position. It can also juxtapose thoughts and actions in a proportionate way that wards off excessive negative justification. As well as building a country in the name of justice for all Indonesian people in a civilized society.